The APPLICATION OF GDSS USING AHP AND BORDA METHODS IN HYDROPONIC PLANT QUALITY DETERMINATION - Nurul Ilmy Husain; St. Hajrah Mansyur; Erick Irawadi Alwi (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2024)
Hydroponic cultivation in Gowa Regency, South Sulawesi, experienced serious failure. This failure occurred during the seeding process, caused by the use of poor quality seeds and a lack of consistent attention and control over the environmental conditions of plant growth. The aim of this research is to apply the AHP and Borda methods in a group decision support system to contribute to determining the best plant quality for hydroponic cultivation. In evaluating plant quality, assessment criteria are used which include leaf growth, stem strength, stem quality, planting media, and use of vitamins. There are also 6 alternative plants being evaluated, namely lettuce, bok choy, kale, kale, spinach and celery leaves. The AHP method is used to outline the hierarchical evaluation of hydroponic plant quality, facilitating priority-based decision making through determining relative weights between criteria. Meanwhile, the Borda method is used to integrate the ratings of the three decision makers, producing reference values for each alternative and helping determine the overall quality of hydroponic plants. The calculation results show that the selected alternative, namely spinach, was ranked first with a value of 10.23, while the alternative lettuce plant was ranked sixth or last with a value of 3.69 as the best quality plant. With these findings, spinach plants are considered an effective solution for hydroponic cultivation in Gowa Regency and can be applied more widely in the context of modern agriculture. So that it can increase the yield and sustainability of hydroponic cultivation in Gowa Regency